A 7-year warranty period for chest pain patients with a non-ischaemic [15O]H2O positron emission tomography: a follow-up of 273 individuals. (20th July 2021) - Jukema, RA; Diemen Van, PA; Driessen, RS; Stuijfzand, J; Raijmakers, PG; Winter De, RW; Ven Van De, PM; Rossum Van, AC; Knaapen, P; Danad, I
Abstract: Funding Acknowledgements: Type of funding sources: None. Background:   A normal perfusion scan is associated with a favourable outcome. The aim of the present study is to determine the warranty period of normal hyperemic myocardial blood flow (MBF) derived with quantitative [15O]H2O positron emission tomography (PET) in symptomatic individuals with cardiovascular risk factors.  Methods: A total of 539 patients referred for baseline adenosine [15O]H2O PET MBF imaging because of suspected coronary artery disease (CAD) were investigated. A PET scan was considered normal if the hyperemic MBF  was > 2.3 ml/min/g.  The warranty period was predefined as < 2% annual event rate. The primary endpoint was a composite of late revascularizations, myocardial infarction and all-cause mortality.   Results: In a total of 273 patients (mean age 57.2 ± 9.1; 34.4% male) with a normal PET scan, 19 events occurred during a median follow-up of 6.8 years (interquartile range 4.9-7.7).  Events included 10 late revascularizations, 2 myocardial infarctions and 7 deaths. The annual event rate exceeded 2% in the 8th year of follow-up, resulting in a warranty period of 7 years  (see Figure 1).  Conclusion: In patients referred for suspected CAD a normal hyperemic perfusion derived by [15O]H2O PET confers a 7-year warranty period against late revascularization, myocardial infarction and all-cause mortality.